THE IMPACT OF JOB STRESS ON TURNOVER INTENTION WITH JOB SATISFACTION AS A MEDIATING VARIABLE AT CV MADE KARYA LOGAM - Ni Made Shinta Dwi Maharani; I Gusti Ayu Dewi Adnyani (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to analyze the mediating role of job satisfaction in the effect of job stress on turnover intention among employees of CV Made Karya Logam. The study employs a saturated sampling technique with a total sample of 43 employees. Data were collected using questionnaires and interviews, and analyzed using descriptive statistics and inferential statistical tools with path analysis assisted by SPSS software. The findings reveal that job stress has a positive effect on turnover intention, a negative effect on job satisfaction, and that job satisfaction negatively affects turnover intention. Job satisfaction is proven to partially mediate the relationship between job stress and turnover intention.